Dampak Komitmen Organisasi Terhadap Ketepatan Waktu Pelaporan Keuangan: Peran Sistem Akuntansi Keuangan Daerah Sebagai Variabel Moderasi - Ihyani, Layali; Saputra, Sahdan; Mubin, Miftahul; Marlina, Febria Nurmelia; Marswandi, Ega Dwi Putri (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to determine the effect of Organizational Commitment on Timeliness of Financial Reporting with the Regional Financial Accounting System as Moderation. This research is a correlational quantitative study with a sample size of 90 respondents at the Regional Apparatus Organization of the West Nusa Tenggara Provincial Government. The data analysis method uses moderated regression analysis (MRA). The results stated that organizational commitment affects the timeliness of financial reporting significantly positively. However, the regional financial accounting system does not interact with organizational commitment to affect the timeliness of financial reporting. This is an input for stakeholders in terms of financial reporting both at the provincial and central levels.